Study On Image Authentication Techniques - Vinitha, C; Azath, M (International Journal of Computer Sciences and Engineering, 2014)
Image authentication is the process of proving an image, is an accurate representation of the original one. Image authentication techniques have recently gained great attention due to its importance of multimedia applications. Through non-secure channels like internet digital images are increasingly transferred. Several methods which include Fragile Water-marking, Semi Fragile Water-Marking, Conventional Cryptography are used to protect the authenticity of images. Methods are classified according to the service they provide, that is strict authentication, localization, selective authentication, tamper detection and reconstruction capabilities and robustness against different desired image processing operation. The main aim of the paper is to present a survey and comparison of emerging techniques for image authentication.